Effect of spiritual intelligence training on nurses' skills for communicating with patients - an experimental study - Mansour Arad; Leyla Alilu; Hosein Habibzadeh; Hamidreza Khalkhali; Rasoul Goli (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Since poor communication with the patient has a negative impact on the quality of nursing care, taking the necessary measures to strengthen the relationship with the patient seems necessary. This study was conducted to determine the effect of spiritual intelligence training on nurses' skills for communicating with patients. MATERIALS AND METHODS: This experimental study with the control group and the pretest-posttest design was conducted on 70 nurses working in Imam Khomeini Hospital, Mahabad, in 2019. Randomized stratified sampling was used to recruit participants. Then, participants were randomly assigned to the two groups of control and intervention. The demographic information form and the patient-nurse communication skill questionnaire were used to collect the data. For the intervention group, 7 spiritual intelligence training sessions were held as a workshop in 2 months. Two weeks and a month after the intervention, both groups completed the questionnaires. Data were analyzed with the SPSS software version 17.0. RESULTS: The findings showed that the mean communication skill scores in the intervention group before training were 44.71 ± 7.62, which significantly increased to 66.22 ± 8.43 2 weeks after training. Bonferroni multiple comparisons showed the mean communication skill scores significantly increased before, 2 weeks later and in the follow-up phase in the intervention group (P < 0.001). CONCLUSION: Spiritual intelligence training is effective in improving the communication skills of nurses. It is recommended that the prepared content can be provided to in-service training units; consequently, nurses can improve their communication skills by individual and group learning.